Isolation, lytic activity, and genomic characterization of hospital wastewater phages infecting Mycobacterium smegmatis, a surrogate for tuberculosis bacteria - RINA HIDAYATI PRATIWI; RIRI NOVITA SUNARTI; ARIF NURKANTO; DASMO DASMO; HANUM ISFAENI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Pratiwi RH, Sunarti RN, Nurkanto A, Dasmo, Isfaeni H. 2026. Isolation, lytic activity, and genomic characterization of hospital wastewater phages infecting Mycobacterium smegmatis, a surrogate for tuberculosis bacteria. Biodiversitas 27 (6): d270613. https://doi.org/10.13057/biodiv/d270613. In Indonesia, Tuberculosis (TB) remains a major public health problem, with increasing case numbers and high mortality rates. The increasing prevalence of drug-resistant tuberculosis has encouraged exploration of bacteriophages as alternative antibacterial agents. This study aimed to isolate and characterize lytic bacteriophages from hospital wastewater capable of infecting Mycobacterium smegmatis, a surrogate host commonly used in tuberculosis-related research. Wastewater samples were collected from several hospital sewage outlets in Palembang and subjected to enrichment and plaque assay screening using M. smegmatis as the host bacterium. Three lytic bacteriophage isolates, designated HS, BR, and CH, were successfully obtained and characterized based on plaque morphology, phage titers, and lytic activity. All exhibited clear, small plaques (≈1.0 mm) characteristic of lytic morphology, with titers ranging from 2.3×10⁵ to 2.9×10⁵ PFU/mL. The lytic activity assay revealed that all phages significantly reduced bacterial growth within 10 hours. The CH phage achieved the highest inhibitory effect, reducing bacterial optical density (OD600) by 21%, compared to 14% reductions by HS and BR phages. Notably, CH phage-initiated lysis as early as the first hour, indicating a short latency period and strong infectivity. These results demonstrate that hospital wastewater is a promising source of mycobacteriophages with potential therapeutic value against mycobacterial infections. Among the isolates obtained, CH showed the most promising lytic performance and genomic characteristics, suggesting its potential for further investigation in bacteriophage-based strategies against mycobacterial infections. The WGS analysis demonstrates that the isolated bacteriophage represents a TehO-like phage lineage with high genomic similarity to several Pseudomonas bacteriophages. Genome analysis of the isolated bacteriophage revealed a modular genome organization characteristic of dsDNA bacteriophages, containing structural genes, DNA replication genes, and a lysis module encoding an endolysin.